Comparison of methods to detect Escherichia coli heat-labile enterotoxin in stool and cell-free culture supernatants. - Morgan, D R (1983)
We compared the standard Y-1 adrenal cell (YAC) assay for heat-labile enterotoxin (LT) with newer rapid and economical immunological methods of detection. Stool samples were collected from 164 acutely ill American students in Guadalajara, Mexico. Supernatants were prepared from each stool. Stools were cultured for Escherichia coli by standard techniques. Individual E. coli-like colonies were examined for LT production by the Biken assay. Culture supernatants and stool supernatants were assayed for the presence of LT by the YAC assay, counterimmunoelectrophoresis, and enzyme-linked immunosorbent assay (ELISA). Standard YAC assays of culture supernatants revealed that 40 of the 164 specimens (24%) were LT positive. Counterimmunoelectrophoresis detected 60% and ELISA detected 65% of the 40 known positives when culture supernatants were used. The Biken assay detected 35% of the 40 known positives. With stool supernatants, the YAC assay detected only 18% of the known positives, counterimmunoelectrophoresis detected 60%, and ELISA detected 90%. In addition, ELISA detected 13 LT-positive stool supernatants not detected by the YAC assay of culture supernatants. The ELISA in which stool supernatants are used may be a useful method to detect LT.